2021
DOI: 10.4314/aas.v18i2.7
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Education Environment at the University of Nairobi, Kenya: An Assessment with the DREEM Tool

Abstract: Background: The supportive learning environment can enhance impartating of knowledge and skills. Objective: To assess the learning environment at the School of Medicine of the University of Nairobi using the Dundee Ready Educational Environment Measure(DREEM) tool. Methods: A cross-sectional survey carried in 2019 out among medical students during their clinical years to obtain their perceptions about the learning environment at the School of Medicine of the University of Nairobi. The DREEM tool wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…In contrast to our study's findings, research conducted among medical students in Korea and University of Nairobi revealed a negative perception of their learning environment, as evidenced by total mean scores of 94.65 and 93.3 out of 200, respectively (23,24). The disparity in mean overall scores may be attributed to variations in curriculum types and program durations.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our study's findings, research conducted among medical students in Korea and University of Nairobi revealed a negative perception of their learning environment, as evidenced by total mean scores of 94.65 and 93.3 out of 200, respectively (23,24). The disparity in mean overall scores may be attributed to variations in curriculum types and program durations.…”
Section: Discussioncontrasting
confidence: 99%
“…A total score of 145 has been reported from a medical school in Sweden (17) ,137 from Australia (18). 90.8 from Morocco (19) and 93.3 from Kenya (20). A study from another University, in Khartoum, Sudan (21) showed the total DREEM score was 91.6.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have evaluated this effectiveness using the Dundee Ready Education Environment Measure (DREEM). 28,29,30,31 -X. Scoring of reflectors for the domain "Social Self-Perception" Most of the reflectors, 63.39% marked social self-perception as not too bad.…”
Section: Discussionmentioning
confidence: 99%